Penurunan Glukosa Darah Pasien Diabetes Mellitus Karena Mengkudu Di Puskesmas Siulak Mukai - Putri Dafriani; Mutiara Karamika; Siska Sakti Anggraini; Roza Marlinda (BIOEDUSCIENCE, 2020)
Background: Diabetes Mellitus is a chronic metabolic disorder caused by insulin resistance. Noni juice has the potential as herbal medicine which believed to reduce blood glucose levels. This study aims to determine the effect of noni juice on blood sugar levels on diabetic patients. Methods: This study used 16 respondents. They divided two groups, a control group and a treatment group. Each group consists of 8 respondents. The intervention group received 150 ml of noni juice which was given once a day for ten days. Glucose testing was carried out by the glucose-check method. The blood was taken from the respondent's fingertips capillary. The blood glucose levels between the control group and the intervention group were analyzed using independent t-test. Results: The average blood glucose level in the intervention group was 199.88 mg/dl, while the control group was 326.25 mg/dl. The test results of the mean blood glucose levels between the control group and the intervention group had a significant difference with a value of p = 0.003 (p ≤ 0.05). This indicates a significant effect between blood glucose levels in the control group and the intervention group. Conclusion: Noni can reduce blood glucose levels because it contains flavonoid. It has a hypoglycemic effect. Health workers can suggest consuming noni juice to decrease blood glucose in diabetic patients.